RELIGIOUS VALUES IN INDONESIA’S CHARACTER EDUCATION - Ahmad Nadhif (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This study aims at investigating the ideology behind the positioning of religion included in the Guidance of Culture and Character of the Nation of the Ministry of Education published in 2010. It is presented as part of the curriculum of character education and prescribes for teachers on how to conduct the implantation of good moral values in their students’ mind and heart. This issue of character education marks a significant shift in Indonesia’s national curriculum of education showing a potential to be a conflicting battleground of ideologies. Hence, this is an essential issue to study, especially in the light of Critical Discourse Analysis (CDA). By using three dimensional models of CDA’s Fairclough (1989) the Indonesia’s curriculum of character education is textually analyzed. The result of analysis shows that the use of religious values may still be questionable; in terms of symbols and jargons, religion is highly valued; however, it seems to be only a disguise to silently suppress and marginalize its essential core of teachings.